When I dream of heaven : Angelina's story - Kroll, Steven (Lincolnwood, Ill. : Jamestown Publishers, 2000)
In 1895 in New York City, Gina, a fourteen-year-old Italian immigrant, forced by her family to drop out of school and work long hours in a garment factory, tries to break free of the control her parents have over her finances and social life.
Keywords: Italian Americans -- Juvenile fiction; Italian Americans -- Fiction; Immigrants -- Fiction; Self-confidence -- Fiction; Factories -- Fiction; Conduct of life -- Fiction; New York (N.Y.) -- History -- 1865-1898 -- Fiction